2022
DOI: 10.2113/2022/1308487
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Intrusion-Retreat Processes and Groundwater Evolution in Intruded Coastal Aquifers with Land Reclamation: A Case Study of Eastern Jiangsu, China

Abstract: The hydrogeochemical analysis and numerical simulation were conducted to explore the impact of land reclamation on submarine groundwater discharge and groundwater evolution in the seawater intrusion-retreat processes in eastern Jiangsu, China. The hydrogeochemical results indicated that the origin of salt in most groundwater is saltwater mixing, and weathering-dissolution of minerals enriches the salt in fresh groundwater. The evolution path of coastal groundwater in Jiangsu is Ca-Na-HCO3-Cl → Ca-Na-Cl-HCO3 → … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…While such a role of the low‐ K sr reclamation soil becomes weaker for large tidal amplitudes (e.g., A = 1.5 and 2.0 m), as the intrusion lengths are larger than those in the other two cases. Several studies have reported that land reclamation would mitigate seawater intrusion by moving the saltwater‐freshwater interface seaward (Abd‐Elhamid et al., 2020; Chen & Jiao, 2007; Xiong et al., 2022). However, the findings from Figure 6b indicate that seawater intrusion may not be necessarily alleviated by land reclamation, particularly when the reclamation soil is less permeable and the tidal amplitude is large.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While such a role of the low‐ K sr reclamation soil becomes weaker for large tidal amplitudes (e.g., A = 1.5 and 2.0 m), as the intrusion lengths are larger than those in the other two cases. Several studies have reported that land reclamation would mitigate seawater intrusion by moving the saltwater‐freshwater interface seaward (Abd‐Elhamid et al., 2020; Chen & Jiao, 2007; Xiong et al., 2022). However, the findings from Figure 6b indicate that seawater intrusion may not be necessarily alleviated by land reclamation, particularly when the reclamation soil is less permeable and the tidal amplitude is large.…”
Section: Resultsmentioning
confidence: 99%
“…However, in situations of large tidal amplitudes (e.g., A = 2.0 m), the seaward retreat of SW is more prominent in the aquifer reclaimed by more permeable soils. The comparison in Figure 6b demonstrates rather close seawater intrusion Chen & Jiao, 2007; Xiong et al, 2022). However, the findings from Figure 6b indicate that seawater intrusion may not be necessarily alleviated by land reclamation, particularly when the reclamation soil is less permeable and the tidal amplitude is large.…”
Section: Salinity Distributionsmentioning
confidence: 85%
“…The monitoring target of seawater intrusion is the change in the intrusion transition zone or interface, with indirect reflection factors including changes in vegetation cover, degree of soil salinity, etc., and direct reflection factors including the chemical characteristics of groundwater, groundwater table (or water head), etc. [21,22]. Monitoring methods mainly include the Water Chemical Sampling Analysis Method, Isotope Hydrogeochemical Method, Fixed-point Well Monitoring Method, and Geophysical Monitoring Method (Table 1) [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%